The domino effect [large type] - Bunn, T. Davis, 1952- (Center Point Large Print, 2016)
"Risk analyst Esther Harding has uncovered a conspiracy with the potential to devastate the world's financial markets! But when she sounds the alarm, she wonders who will believe her. As public support grows for her ideas, so does the desperation of those whose greed she seeks to expose"--